The Spatial Lag X Method Using Three Types of Distance Weighting in Food Security Data Analysis in Central Sulawesi - Mbete, Roselina Lucia Ketty; Miswanto; Biyanto, Frasto; Siregar, Baldric (PT FORMOSA CENDEKIA GLOBAL, 2025)
Food security is a critical global issue due to rapid population growth and the increasing impacts of climate change. This study aims to analyze food security and identify spatial patterns among regions in Central Sulawesi in 2022. A Spatial Lag X method was applied, enhanced with three distance weighting techniques: Inverse Distance Weighting (IDW), Exponential Distance Decay (EXP), and Double Power Distance (DPD). These were used to assess the spatial influence on food security data, sourced from the Central Sulawesi Statistics Bureau. The Spatial Lag X approach integrates neighboring regions’ variables to explain the dependent variable. The findings reveal that with IDW and EXP weights at a 10% significance level, no variables significantly influenced the Food Security Index. However, using DPD weights, Gross Regional Domestic Product (GRDP) per capita at current prices (X4) significantly influenced the Food Security Index at a 10% level. The DPD-weighted Spatial Lag X model was identified as the best model for analyzing food security in Central Sulawesi in 2022, achieving an AIC value of 23.91885 and an R² of 0.9977. This study highlights the importance of spatial factors in understanding regional food security dynamics.